2017
DOI: 10.3892/mmr.2017.7575
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miRNA-21 is a promising biomarker for heart failure

Abstract: microRNA 21 (miRNA‑21) promotes the development of cardiac fibrosis, hypertrophy and heart failure. However, whether it can be used as a biomarker for the diagnosis and prognosis of heart failure remains unclear. The current study assessed circulating miRNA‑21 as a viable indicator for diagnosis and prognosis of heart failure. The levels of miRNA‑21 and brain natriuretic peptide were measured in serum obtained from the peripheral vein (miRNA‑21‑PV) and coronary sinus (miRNA‑21‑CS) of 80 patients with heart fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 36 publications
2
46
0
1
Order By: Relevance
“…Previously, by searching the Medline database we identified a large scale of microRNAs playing a role in pathogenesis of diabetes mellitus and cardiovascular/cerebrovascular diseases. Finally, we selected for the study a shortlist of 29 microRNAs demonstrated repetitively by numerous scientific teams to be associated with normal stages (development and homeostasis of the cardiovascular system, angiogenesis, and adipogenesis) and pathological conditions and diseases (vascular endothelial dysfunction and inflammation, hypoxia, hypertension and regulation of hypertension-related genes, obesity, dyslipidaemia, atherosclerosis and atherosclerotic plaque formation, insulin resistance, diabetes mellitus and diabetes-related complications, metabolic syndrome, cardiovascular diseases involving the blood vessels (coronary and peripheral artery diseases, carotid artery disease, pulmonary arterial hypertension, cerebrovascular disease, aortic and intracranial aneurysms), cardiovascular diseases involving the heart (congenital heart disease, cardiomyopathies, cardiac dysrhythmias, hypertensive heart disease, myocardial disease, valvular heart disease, inflammatory heart disease, rheumatic heart disease, pulmonary heart disease, and heart failure), chronic kidney disease, ischemia/reperfusion injury, cardiac regeneration and cachexia) ( Table 1 ) [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ,…”
Section: Introductionmentioning
confidence: 99%
“…Previously, by searching the Medline database we identified a large scale of microRNAs playing a role in pathogenesis of diabetes mellitus and cardiovascular/cerebrovascular diseases. Finally, we selected for the study a shortlist of 29 microRNAs demonstrated repetitively by numerous scientific teams to be associated with normal stages (development and homeostasis of the cardiovascular system, angiogenesis, and adipogenesis) and pathological conditions and diseases (vascular endothelial dysfunction and inflammation, hypoxia, hypertension and regulation of hypertension-related genes, obesity, dyslipidaemia, atherosclerosis and atherosclerotic plaque formation, insulin resistance, diabetes mellitus and diabetes-related complications, metabolic syndrome, cardiovascular diseases involving the blood vessels (coronary and peripheral artery diseases, carotid artery disease, pulmonary arterial hypertension, cerebrovascular disease, aortic and intracranial aneurysms), cardiovascular diseases involving the heart (congenital heart disease, cardiomyopathies, cardiac dysrhythmias, hypertensive heart disease, myocardial disease, valvular heart disease, inflammatory heart disease, rheumatic heart disease, pulmonary heart disease, and heart failure), chronic kidney disease, ischemia/reperfusion injury, cardiac regeneration and cachexia) ( Table 1 ) [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ,…”
Section: Introductionmentioning
confidence: 99%
“…In combination with other researchers 'statistics on sample size, we selected more than 60 healthy samples and more than 60 cases of heart failure. Exhaustion samples were analyzed [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. As shown in Figure 1, the aim of the present study was to identify circulating miRNAs in human plasma as biomarkers for the diagnosis of heart failure and its related diseases, to assess the appropriate biomarkers for identifying key characteristics of miRNAs, and to analyze their performance.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there was no signi cant difference between preoperative and postoperative miR-21-5p levels in patients with coronary artery disease (p < 0.05). These results were found to be different according to the literature data that miR-21 levels were higher in patients with coronary artery disease and heart failure compared [19][20][21][22][23]. This difference may be thought to occur because miR-21-5p levels correlate with cardiac markers.…”
Section: Discussionmentioning
confidence: 73%
“…MiR-21 levels are high in unbalanced angina patients [20] and atherosclerosis model mice [21]. Patients with heart failure have high levels of miR-21, brain natriuretic peptide and miR-21 in serum samples collected from both the peripheral vein and coronary sinus [22]. In patients suffering from acute myocardial infarction, there is a strong correlation between miR-21 and cardiac markers such as cardiac troponin, CK and CK-MB [23].…”
Section: Discussionmentioning
confidence: 99%